2016
DOI: 10.1128/jvi.02320-15
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus Inhibitor-of-Apoptosis Op-IAP3 Blocks Apoptosis by Interaction with and Stabilization of a Host Insect Cellular IAP

Abstract: Baculovirus-encoded inhibitor of apoptosis (IAP) proteins likely evolved from their host cell IAP homologs, which function as critical regulators of cell death. Despite their striking relatedness to cellular IAPs, including the conservation of two baculovirus IAP repeat (BIR) domains and a C-terminal RING, viral IAPs use an unresolved mechanism to suppress apoptosis in insects. To define this mechanism, we investigated Op-IAP3, the prototypical IAP from baculovirus OpMNPV. We found that Op-IAP3 forms a stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 64 publications
(125 reference statements)
0
31
0
Order By: Relevance
“…Such scenarios resemble the mechanism by which Orgyia pseudotsugata multiple nucleopolyhedrovirus (OpMNPV) inhibitor-of-apoptosis protein 3 (IAP-3) inhibits baculovirus replication-induced apoptosis in host cells. Rather than binding to and inhibiting activator caspases directly, OpMNPV IAP-3 binds and stabilizes host cell IAP, which in turn continues to prevent the onset of apoptosis [63]. …”
Section: Resultsmentioning
confidence: 99%
“…Such scenarios resemble the mechanism by which Orgyia pseudotsugata multiple nucleopolyhedrovirus (OpMNPV) inhibitor-of-apoptosis protein 3 (IAP-3) inhibits baculovirus replication-induced apoptosis in host cells. Rather than binding to and inhibiting activator caspases directly, OpMNPV IAP-3 binds and stabilizes host cell IAP, which in turn continues to prevent the onset of apoptosis [63]. …”
Section: Resultsmentioning
confidence: 99%
“…its anti-apoptosis by binding to its targeted cellular IAP. 26,27 In this study, the amino acid sequence before the BIR1 domain in Ac-IAP2 was extremely short, that is, Ac-IAP2 didn't have the N-terminal "leader", which suggested that Ac-IAP2 was likely to have the same anti-apoptotic mechanism as Op-IAP3. Of course, its RING domain also needed to have E3 ubiquitin ligase activity.…”
Section: Bir2 Domain In Ac-iap2 Was Essential For Its Antiapoptotic Fmentioning
confidence: 94%
“…27 According to this presumption, if the RING domain of Ac-IAP2 also had E3 ubiquitin ligase activity, the 8 lysine residues in its BIR2 domain (Fig. 5A), which were not existed in the BIR2 domain of Ac-IAP1, were completely unable to enhance its anti-apoptotic function.…”
Section: Bir2 Domain In Ac-iap2 Was Essential For Its Antiapoptotic Fmentioning
confidence: 99%
“…For example, in Drosophila cells infected with FHV activation of p53 leads to induction of the pro-apoptotic gene reaper that blocks the activity of IAPs [19]. In baculovirus infected Lepidopteran cells, inhibition of host translation leads to depletion of cellular IAPs, whose stability is tightly regulated [18]. Indeed, Lepidopteran and Drosophila IAPs contain N-terminal instability motifs that are targeted by different signaling pathways in response to virus infection [47].…”
Section: Host Antiviral Pathways Targeted By Insect Virusesmentioning
confidence: 99%
“…Unlike their cellular counterparts, vIAPs lack an N-terminal instability motif [47]. As a result, they act by stabilizing cellular IAPs, thus preventing apoptosis in infected cells as recently shown for the prototypical baculovirus Op-IAP3 from Orgya pseudotsugata multiple nucleopolyhedrovirus [18]. The p35 suppressor from Autographa californica multiple nucleopolyhedrovirus functions as a substrate for effector caspases such as DRICE, while the related p49 suppressor from Spodoptera littoralis nucleopolyhedrovirus has the potential to block both initiator and effector caspases [48].…”
Section: Host Antiviral Pathways Targeted By Insect Virusesmentioning
confidence: 99%